If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 1Y = 0 Reorder the terms: 1Y + 4y = 0 Solving 1Y + 4y = 0 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-4y' to each side of the equation. 1Y + 4y + -4y = 0 + -4y Combine like terms: 4y + -4y = 0 1Y + 0 = 0 + -4y 1Y = 0 + -4y Remove the zero: 1Y = -4y Divide each side by '1'. Y = -4y Simplifying Y = -4y
| 3x-45=8x | | 2x-30=-x | | -6+m=9 | | 5p^4-2q^4-10=0 | | -7x-2y=11 | | -9+x=14 | | -8x-4=16 | | 3n^2-12n+9=0 | | 8+5x=42 | | j+(-7)=-1 | | 4*2/3-1 | | p-(-7)=-2 | | 3x+99=-2x-1 | | 81m^4+106m^2+25=0 | | (-10)+m=(-2) | | -5x+68=-7x+8-3x | | 5.5=10em-5 | | -17+x=-12 | | r-5=-1 | | 3x+77=-6x-4 | | m-5=12-9+1 | | -3+y=19 | | 0=16t^2+8t+15 | | -12x-17=-13x+7+9x | | -10x^2-27xy-5y^2=0 | | 7x^2-56x-21=0 | | 0.02(60)+0.04x=0.03(50+x) | | -5x^2+6x+6=0 | | k-3=24 | | -x^2+2x-8=0 | | a+2(4+2a-c)-4c+2=0 | | v+9=U |